Un accord pour la biodiversité marine : le cas du parc naturel marin de l’estuaire de la Gironde et de la mer des Pertuis - Sophie Lafon (VertigO)
Marine conservation is now an international issue. Protected marine areas are now a tool strongly discussed. In this study, the process of dialogue which took place during the creation of a recent park, the Pertuis and Gironde natural park in southwest France is analysed, in April 2015. Our research analyzes the different steps in the talk relating to the implementation of the marine park, and observes the appropriation of issues (especially environmental issues) by participants. This paper demonstrates that the dialogue process allows the co-construction of knowledge socio-économic and environnemental, especially for fish resources. The research identifies how the different sources of friction throughout the process contributed to the decision.